Do soil‐borne fungal pathogens mediate plant diversity–productivity relationships? Evidence and future opportunities. (3rd April 2020) - van Ruijven, Jasper; Ampt, Eline; Francioli, Davide; Mommer, Liesje
Abstract: From the establishment of the first biodiversity experiments in the 1990s, studies have consistently reported positive relationships between plant diversity and productivity in grasslands. However, the predominant hypotheses that may explain this pattern have changed. Initially, there was a strong focus on plant–plant interactions such as facilitation and resource partitioning, but the results from the first experiments that manipulated soil communities have led to a paradigm shift. In the current view on mechanisms that drive plant diversity–productivity relationships, fungal pathogen‐induced reductions of plant productivity at low diversity play an important role. This role rests on two assumptions: the effects of pathogens (a) are plant‐species specific (i.e. not all plant species are affected equally by a fungal pathogen) and (b) display negative density dependence (i.e. decrease with decreasing host plant density and hence, with increasing plant species richness). Here, we review the empirical evidence for these two assumptions. In the biodiversity literature, this is mainly based on indirect approaches, such as soil sterilization, plant–soil feedback studies and plant biomass patterns. The identification and functional characterization of the fungal pathogens that actually drive the plant diversity–productivity relationship have only recently started. Synthesis . Nevertheless, these studies, together with studies on plant–pathogen interactions in agricultural crops and forests, clearly suggest host‐specific, negative density‐dependent effects of fungal pathogens are common. Moreover, recent studies suggest that the reduced impact of pathogens at high plant diversity depends not just on host density but also on effects of neighbouring (non‐host) plant species on the pathogen. Understanding how neighbouring plants affect the interactions between a pathogen and its host plants and disentangling the role of plant–pathogen interactions from other mechanisms potentially driving diversity–productivity relationships are important future challenges. Abstract : Soil‐borne fungal pathogens may drive the positive plant diversity–productivity relationship by reducing plant productivity at low diversity. Although the characterization of these fungal pathogens in grasslands has only recently started, our review of studies using indirect approaches, such as soil sterilization and plant biomass patterns, and studies of plant–pathogen interactions in agricultural crops and forests, clearly suggest host‐specific, diversity‐dependent effects of fungal pathogens are common. Understanding how neighbouring plants affect plant‐pathogen interactions and disentangling the role of plant–pathogen interactions from other mechanisms potentially driving diversity–productivity relationships are important future challenges.